2021
DOI: 10.20473/ijtid.v9i1.22160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Based on Detection of CXCL10 in Urine as Biomarker for The Determining Diagnosis of Active Lung Tuberculosis

Abstract: Tuberculosis diagnosis is an important component in decreasing TB incidence and prevalence. Because of the difficulty to collect sputum in some cases, urine specimens are used as it is easier to garner. One of the biomarkers in urine that can be used to diagnose pulmonary TB is IP-10, which can be represented by the CXCL10 gene. The study aims to determine the accuracy of diagnosis based on detection of the CXCL10 gene in urine as a biomarker for the patients with suspected pulmonary TB in Dr. Soetomo Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Pulmonary tuberculosis is the infectious and the most common form of tuberculosis, occurring in over 80% of cases. 19 A study found that patients who had recently been infected with M tuberculosis caused functional fatigue and reduced CD4+ T cells. This correlation between M. tuberculosis infection and CD4+ T cells which underlies that tuberculosis treatment will correlate with an increase in CD4+ T cells counts.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary tuberculosis is the infectious and the most common form of tuberculosis, occurring in over 80% of cases. 19 A study found that patients who had recently been infected with M tuberculosis caused functional fatigue and reduced CD4+ T cells. This correlation between M. tuberculosis infection and CD4+ T cells which underlies that tuberculosis treatment will correlate with an increase in CD4+ T cells counts.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies has been showed that CXCL10 is associated with a variety of human diseases including infectious diseases, chronic inflammatory disease, and immune dysfunctions ( Mertaniasih et al, 2021 ). This makes CXCL10 currently considered as a diagnostic tool for leprosy, because of its role in their pathogenesis and easily accessible detection method ( Pujiastuti, Agusni & Rahmadewi, 2017 ; Medeiros et al, 2015 ; Mertaniasih et al, 2021 ). Identifying CXCL10 can be convenient through easily accessible lateral flow assays, rendering it a feasible indicator for detecting leprosy ( Van Hooij et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%